Towards a Philosophy of Language Management - David Crystal (Universidad de La Sabana, 2010)
Over the past twenty years, in a number of different domains, I have been preoccupied by the relationship between content and language. Finding myself the editor of a family of general encyclopedias in the late 1980s brought an encounter with "knowledge" which had to be integrated with my professional linguistic concerns. This has since developed to include issues in document classification, search, e-commerce, and Internet security. Other directions of integration emerged in higher education, notably the need for a synergy between linguistic and cultural studies and between language and literature. And accompanying all this has been a major change in public attitudes to language, following the reaction against institutionalized linguistic prescriptivism and the evolution of a fresh understanding of the relationship between standard and nonstandard language. The varied nature of these examples suggests the need to consider the question of integration at an appropriately general level, and it is this - on analogy with established domains such as the philosophy of science or the philosophy of religion - that the title of my paper is intended to address.